ATIM-21. THE CURRENT STATUS OF AD-SGE-REIC GENE THERAPY FOR MALIGNANT GLIOMA. (11th November 2019) - Kurozumi, Kazuhiko; Fujii, Kentaro; Oka, Tetsuo; Shimazu, Yosuke; Hattori, Yasuhiko; Tomita, Yusuke; Uneda, Atsuhito; Matsumoto, Yuji; Tsuboi, Nobushige; Kaneda, Keisuke; Makino, Keigo; Michiue, Hiroyuki; et al.
Abstract: INTRODUCTION: Expression of the gene encoding reduced expression in immortalized cells/Dickkopf-3 ( REIC/Dkk-3 ) was reported to be reduced in a variety of human cancer cells. We previously examined the antitumor effect of an adenoviral vector carrying REIC/Dkk-3 gene (Ad-CAG-REIC). Recently, a novel adenoviral vector expressing REIC/Dkk-3 has also been developed based on the cytomegalovirus promoter-driven super gene expression system (Ad-SGE-REIC). We evaluated the anti-glioma effect of the Ad-SGE-REIC and planned a clinical trial of Ad-SGE-REIC for malignant glioma. MATERIALS AND METHODS: We evaluated a cytotoxicity assay to treatments with Ad-SGE-REIC, Ad-CAG-REIC, or Ad-LacZ (control) using malignant glioma cells. The survival of mice in each group was analyzed by the Kaplan–Meier method. We also performed Good Laboratory Practice (GLP) toxicology tests and prepared a protocol for this clinical trial. RESULTS: In the cytotoxicity assay, after treatment with Ad-SGE-REIC, the number of malignant glioma cells attached to the bottom of culture wells was significantly reduced in a time-dependent manner. Mice treated with Ad-SGE-REIC survived significantly longer than those treated with other vectors. We also performed GLP toxicology tests using intracranial injection of higher doses of Ad-SGE-REIC in rats at Shin Nippon Biomedical Laboratories (SNBL Japan) to determine the injection dose of Ad-SGE-REIC for this clinical trial. After finishing the consultation with Pharmaceuticals and Medical Devices Agency (PMDA), we prepared a protocol for a phase I/IIa clinical trial of Ad-SGE-REIC for the treatment of recurrent malignant glioma supported by Japan Agency for Medical Research and Development (AMED). This protocol was reviewed by institution review board (IRB) in March 2019. We submitted a notification of this trial in April 2019. CONCLUSIONS: We demonstrated the anti-glioma effect of Ad-SGE-REIC. We will start a phase I/IIa clinical trial of Ad-SGE-REIC for the treatment of recurrent malignant glioma.